(untitled) (مجلة جامعة اللاذقية - سلسلة الآداب والعلوم الانسانية, 2019)
The study aims to identify the relationship between psychological happiness and self-control among a sample of students of Damascus University, as well as to identify the significance of differences in both psychological happiness and self-control according to the variable of specialization. The sample of the study consisted of (270) male and female students in Damascus University from the third year. Enrolled for the academic year 2018-2019, they were selected in the available way from theoretical and applied faculties. Psychological happiness and self-control were used in the study. The study found a relationship between psychological happiness and self-control as the correlation coefficient (0.66 **), and the absence of statistically significant differences between the students of theoretical faculties and students of applied colleges in performance on the scale of psychological happiness, While there were differences among them in performance on the scale of self-control in favor of students of theoretical faculties. تهدف الدراسة إلى تعرف العلاقة بين السعادة النفسية وضبط الذات لدى عينة من طلبة جامعة دمشق، كما تهدف إلى تعرف دلالة الفروق في كل من السعادة النفسية وضبط الذات تبعاً لمتغير التخصص الدراسي.تكونت عينة الدراسة من(270) طالباً وطالبة في جامعة دمشق من السنة الثالثة والمسجلين للعام الدراسي 2018-2019، تم اختيارهم بالطريقة المتيسرة من كليات نظرية وكليات تطبيقية.استُخدم في الدراسة أداة السعادة النفسية وأداة ضبط الذات. وتوصلت الدراسة إلى وجود علاقة بين السعادة النفسية وضبط الذات إذ بلغ معامل الارتباط (0.66**)، وعدم وجود فروق دالة إحصائياً بين طلبة الكليات النظرية وطلبة الكليات التطبيقية في الأداء على مقياس السعادة النفسية، بينما وجدت فروق فيما بينهم في الأداء على مقياس ضبط الذات لصالح طلبة الكليات النظرية.